PENINGKATAN HASIL BELAJAR TEMATIK MELALUI TIPE STAD (STUDENT TEAMS ACHIEVEMENT DIVISIONS) PADA SISWA KELAS V SDN CEMPAKA BARU 03 PAGI JAKARTA PUSAT - Siti Patonah; Ati Kusmawati (Khazanah Pendidikan, 2020)
ABSTRACTThis study is entitled Improving Thematic Learning Outcomes Through TypeSTAD ( Student Teams Achievement Divisions ) in Class V Students of SDN CempakaBaru 0 3 Pagi, Central Jakarta. Research conducted in the SDN Cempaka Baru 03 Pagi.This study uses a class action research type with the Kemmis and Mc Taggart modelsapplied in two cycles. In the Pre-Cycle the researchers only used the type of lecture, thelearning outcomes of students got an average grade for Indonesian Language content56.16, and for Science content 61.81. In Cycle I, the researcher teaches students to usethe STAD type and powerpoint media . In this Cycle I, student learning outcomes haveincreased with an average grade for Indonesian Language content 65.68, and forScience content 67.16. In the Cycle II the students can improve their abilities, moresignificantly by obtaining an average score of Indonesian Language content 80.23, andfor Science content 81.48. With the success of learners who passed beyond KKM tocharge Indonesian Language 80.65%, and 87.10% for the Science. By thus can beconcluded that the learning of cooperative types STAD on the theme of Environment OurBest Friends can improve the outcomes of learning of students in class V SDN CempakaBaru 03 Pagi.Keywords: Thematic Learning Outcomes , STAD Type .